Australian beach systems: Are they at risk to climate change?. (1st June 2022) - Short, Andrew D.
Abstract: This paper reviews the past behaviour and present status of Australian beach systems and their likely response to the impacts of climate change in the coming century. The 2021 IPCC AR6 report, besides highlighting rising sea level and changing storm tracks in the Australian region, places high confidence in general recession of most Australian beaches by 2100. However, Holocene barrier studies, decades of field survey data from a number of sites and satellite mapping of the entire coast indicate that 78% of Australia's beaches have been stable over the past 30–40 years. The data also indicate that while some beaches are receding, others are accreting, and the majority are stable. A sea-level tipping point is yet to be reached and these beaches are unlikely to begin recession in the timeframe or on the scale predicted by AR6 during the 21st millennium. The field data also documents considerable variation between beaches, even adjoining beaches, highlighting the need to undertake studies and predictions at a local level. The issue with the AR6 predictions is the simplistic modelling applied on a global scale, which while seemingly attractive, cannot deliver the level of detail required at the local level. In addition, shifting pressure belts and wave climates, may have at least the same, if not a greater magnitude of impact on many beaches, as the sea level rise. In order to make accurate predictions of future beach behaviour a sediment compartment approach is advocated, based on detailed seabed topography, sediment sources and paths, and changing regional wave and tide regimes. It seems unlikely that a single sea level tipping point will trigger widespread recession around Australia, rather sea level in combination with other regional and local factors will determine when and how each beach responds to these impacts. Highlights: Modelling that predicts massive Australian beach retreat is questioned. Most Australian beaches are presently stable. A sea level tipping point is still decades away. Local investigations are required to address and model future changes. A sediment compartment approach to coastal management is recommended.